CARCINOMA OF UTERINE CERVIX WITH MULTIPLE SKULL METASTASES AS THE FIRST PRESENTATION OF RECURRENCE: A CASE REPORT - Praffulla Chandra Rai; Ajeet Kumar Gandhi; Madhup Rastogi; Satyajeet Rath; Sambit Swarup Nanda; Harikesh Bahadur Singh (Medico Research Chronicles, 2018)
Carcinoma of cervix recurring as multiple skull metastasis is a very rare presentation. A 49-yearold woman, a diagnosed case of carcinoma cervix [International Federation of Gynecology and Obstetrics (FIGO) stage IB1] treated with radical hysterectomy presented with generalized seizures to us after 40 months of initial diagnosis. Contrast-enhanced computed tomography showed metastasis to left temporoparietal bone and left frontal bone. Biopsy from the left temporal lesion showed non-keratinizing squamous cell carcinoma. She was thus diagnosed as recurrent carcinoma cervix with multiple calvarial metastases with the controlled primary site. She received palliative radiotherapy to the entire skull. She further received 4 cycles of palliative chemotherapy with paclitaxel and carboplatin repeated every 3 weeks. However, she could not tolerate chemotherapy after 4 cycles owing to significant deterioration of performance status and expired after 12 months of diagnosis of metastasis.